Pathophysiological study of diarrhoea in a patient with medullary thyroid carcinoma. Evidence against a secretory mechanism and for the role of shortened colonic transit time. Issue 4 (April 1988) - Rambaud, J C; Jian, R; Flourié, B; Hautefeuille, M; Salmeron, M; Thuillier, F; Ruskoné, A; Florent, C; Chaoui, F; Bernier, J J
Abstract : Intubation techniques and scintigraphic studies were used to determine the origin and mechanism of diarrhoea in a patient with medullary thyroid carcinoma, high plasma immunoreactive calcitonin and normal circulating serotonin, substance P and prostaglandins E2 and F2 alpha. Normal function of the small intestine was found for the following: (a) absorption tests; (b) water and electrolyte absorption in the proximal jejunum; (c) 24 hour flow rate and composition of fluid entering the colon and (d) gastric emptying rate and small intestinal progression of a normal meal. By contrast, colonic function was markedly impaired in three ways: (a) water absorption was decreased by half; (b) as the main excreted solutes were organic acids, a large electrolyte gap was recorded in faecal water, and (c) colonic transit time of the meal marker was very short, and was in agreement with the rapid transit of ingested radioopaque markers. These data strongly suggest that decreased absorption in the colon secondary to a motor disturbance is the main mechanism of diarrhoea in this case of medullary thyroid carcinoma, while calcitonin induced small intestinal fluid secretion suggested earlier is either non-existent, or only of minor importance.